1995
DOI: 10.1111/j.1432-1033.1995.tb20372.x
|View full text |Cite
|
Sign up to set email alerts
|

Benzoyl‐Coenzyme‐A 3‐Monooxygenase, a Flavin‐Dependent Hydroxylase

Abstract: A new variant of aerobic benzoate degradation has been found in a denitrifying bacterium in which benzoyl‐CoA is the first intermediate [Altenschmidt, U., Oswald, B., Steiner, E., Herrmann, H. & Fuchs, G. (1993) New aerobic benzoate oxidation pathway via benzoyl‐coenzyme A and 3‐hydroxybenzoyl‐coenzyme A in a denitrifying Pseudomonas sp, J. Bacteriol. 175, 4851–4858)]. The initial reaction is catalyzed by benzoate‐CoA ligase (AMP‐forming), converting benzoate into benzoyl‐CoA. The next step is 3‐hydroxylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The assay mixture (600 l) contained 100 mM Tris-HCl (pH 8.5), 2 mM dithiothreitol, 5 mM MgCl 2 , 1 mM ATP, 0.4 mM CoA, 1 mM aromatic acid, and 6 l of crude cell extract. Benzoyl-CoA was measured at 290 nm (ε ϭ 3.9 mM Ϫ1 cm Ϫ1 ), 2-hydroxybenzoyl-CoA was measured at 320 nm (ε ϭ 5.9 mM Ϫ1 cm Ϫ1 ), 3-hydroxybenzoyl-CoA was measured at 310 nm (ε ϭ 3.3 mM Ϫ1 cm Ϫ1 ), 4-hydroxybenzoyl-CoA was measured at 300 nm (ε ϭ 10.55 mM Ϫ1 cm Ϫ1 ), and 2-aminobenzoyl-CoA was measured at 365 nm (ε ϭ 5.5 mM Ϫ1 cm Ϫ1 ) (48,60). For the coupled enzyme assay, AMP formation was monitored by coupling the CoA ligase reaction to the myokinase, pyruvate kinase, and lactate dehydrogenase system and by spectrophotometrically measuring the rate of NADH oxidation at 365 nm (60).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay mixture (600 l) contained 100 mM Tris-HCl (pH 8.5), 2 mM dithiothreitol, 5 mM MgCl 2 , 1 mM ATP, 0.4 mM CoA, 1 mM aromatic acid, and 6 l of crude cell extract. Benzoyl-CoA was measured at 290 nm (ε ϭ 3.9 mM Ϫ1 cm Ϫ1 ), 2-hydroxybenzoyl-CoA was measured at 320 nm (ε ϭ 5.9 mM Ϫ1 cm Ϫ1 ), 3-hydroxybenzoyl-CoA was measured at 310 nm (ε ϭ 3.3 mM Ϫ1 cm Ϫ1 ), 4-hydroxybenzoyl-CoA was measured at 300 nm (ε ϭ 10.55 mM Ϫ1 cm Ϫ1 ), and 2-aminobenzoyl-CoA was measured at 365 nm (ε ϭ 5.5 mM Ϫ1 cm Ϫ1 ) (48,60). For the coupled enzyme assay, AMP formation was monitored by coupling the CoA ligase reaction to the myokinase, pyruvate kinase, and lactate dehydrogenase system and by spectrophotometrically measuring the rate of NADH oxidation at 365 nm (60).…”
Section: Methodsmentioning
confidence: 99%
“…Benzoate-CoA ligase activity was determined at 30°C with crude cell extracts through a direct spectrophotometric assay or via a coupled enzyme assay. For the direct assay, product formation (CoA derivatives) was monitored spectrophotometrically as described previously (48). The assay mixture (600 l) contained 100 mM Tris-HCl (pH 8.5), 2 mM dithiothreitol, 5 mM MgCl 2 , 1 mM ATP, 0.4 mM CoA, 1 mM aromatic acid, and 6 l of crude cell extract.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, some dehalogenation mechanisms of aromatic compounds also involve CoA thioester formation in aerobiosis (81). Although the rationale for utilizing such hybrid pathways, i.e., aerobic catabolic pathways endowed with typical features of an anaerobic catabolism, is not known, it has been suggested that they could represent a strategy of the microorganisms to cope with fluctuations of oxygen supply (212). In this sense, the existence of a hybrid pathway for the catabolism of PA in E. coli could reflect the facultative anaerobic character of this bacterium.…”
Section: Pa Aerobic Hybrid Pathwaymentioning
confidence: 99%
“…strain B4 suggested gentisyl-CoA as an intermediate and thus a possible role for gentisyl-CoA thioesterase (11). Also, the first steps of a novel benzoate aerobic degradation pathway observed in a denitrifying bacterium may involve transformation of benzoate to benzoyl-CoA, benzoyl-CoA to 3-hydroxybenzoyl-CoA, and 3-hydroxybenzoyl-CoA to gentisyl-CoA (1,19). Finally, it has been postulated that gentisyl-CoA is formed from 4-hydroxbenzoyl-CoA in halophilic Archaea via the action of a novel monooxygenase that catalyzes intramolecular thioester group migration (i.e., the NIH shift) (6).…”
Section: Chemicalsmentioning
confidence: 99%